Analisis Hukum Tindak Pidana Korupsi Pemerintah Desa Pada Proyek Pembangunan Bendungan Paselloreng Kecamatan Gilireng - Andi Wahyuddin Nur; Andi Bau Mallarangeng; Putri Anisa Nurfadillah (Legal Journal of Law, 2025)
The purpose of this study was to determine the form of corruption committed by the village head in land acquisition for the construction of the Paselloreng Dam in Gilireng District and how the application of the elements of the crime to the actions of the perpetrators of corruption in the land acquisition of the project. The study used two methods, namely 1) normative legal research, by taking legal data sources and secondary data by processing data from primary, secondary, and tertiary legal materials, 2) qualitative research with field research, through observation and interviews with respondents. The results of this study indicate that the form of corruption committed by the perpetrators in land acquisition for the construction of the Paselloreng Dam is a criminal act of corruption that is detrimental to state finances or the state economy by abusing the authority, opportunity, or means available to him because of the position or position attached to him, as the power of attorney for the seller of the land the defendant did not convey the actual facts regarding the identity of the land buyer and the budget available in the land acquisition activity. The application of the elements of corruption committed by the perpetrators of land acquisition based on the decision of the panel of judges describes each element of the article contained in Article 3 of Law Number 31 of 1999 concerning the eradication of criminal acts of corruption. Which elements are linked to the facts revealed in court, both from the evidence and physical evidence.